2017
DOI: 10.1002/mp.12176
|View full text |Cite
|
Sign up to set email alerts
|

A simple formulation for deriving effective atomic numbers via electron density calibration from dual-energy CT data in the human body

Abstract: The DEEDZ conversion method based on the simple formulation proposed could facilitate the construction of ρ and Z images from acquired DECT data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 25 publications
4
47
0
Order By: Relevance
“…Very recently, we proposed a new, simpler conversion method (which we called DEEDZ) to obtain Z eff images from DECT data, via q e calibration. 7 By performing numerical analysis, we showed that the DEEDZ conversion yielded Z eff values that were in excellent agreement with the reference values. The main objective of this study is to propose an alternative empirical parameterization for the correlation between I-value and Z eff , and to present a simplified formulation for deriving SPR from DECT data via the DEEDZ conversion (hereafter, we refer to this method as "DEEDZ-SPR").…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…Very recently, we proposed a new, simpler conversion method (which we called DEEDZ) to obtain Z eff images from DECT data, via q e calibration. 7 By performing numerical analysis, we showed that the DEEDZ conversion yielded Z eff values that were in excellent agreement with the reference values. The main objective of this study is to propose an alternative empirical parameterization for the correlation between I-value and Z eff , and to present a simplified formulation for deriving SPR from DECT data via the DEEDZ conversion (hereafter, we refer to this method as "DEEDZ-SPR").…”
Section: Introductionsupporting
confidence: 69%
“…7,8 Here, HU k is the CT number in Hounsfield units for high-kV (k = H) and low-kV (k = L) scans, which is related to the so-called "reduced CT number", u k = HU k / 1000 + 1. a is the weighting factor for subtraction and c L is the proportionality constant for the low-energy u L data. These two can be regarded as material-independent but scanner-and protocol-specific fit parameters.…”
Section: A Derivation Of Spr From Dect Data Via Q E and Z Eff Calimentioning
confidence: 99%
See 2 more Smart Citations
“…Several formalisms for converting CT numbers from DECT to SPR were proposed in literature. Most of these formalisms are parameter‐based and aim at the extraction of ED and effective atomic number (EAN) or photon absorption cross section, which are used to estimate the mean excitation energy ( I ‐value) or the stopping number, respectively. Alternative methods parameterize the I ‐value or the SPR directly, while other groups focus on calibrating pseudo‐monoenergetic images derived from DECT to predict the SPR of tissues .…”
Section: Introductionmentioning
confidence: 99%